The Influence of Fanaticism and Cohesiveness on the Tendency of Aggression Behavior of Panser Biru PSIS Semarang Football Supporters - Devi Asterina Anggraini; Siska Adinda Prabowo Putri; illuminata Rheny Arum Permitasari (Universitas Medan Area, 2023)
The purpose of this study was to find a relationship between fanaticism and cohesiveness towards the tendency of aggression behavior in PSIS Semarang Panser Biru football supporters. The sample used was 357 PSIS Semarang Panser Biru football supporters. The sampling technique uses purposive sampling. Data analysis using multiple regression. The results of this study show that there is a relationship between fanaticism and cohesiveness towards the tendency of aggression behavior, there is a positive relationship and significance between fanaticism towards the tendency of aggression behavior and there is a positive relationship and significance between cohesiveness towards the tendency of aggression behavior.